2015
DOI: 10.1123/jpah.2013-0391
|View full text |Cite
|
Sign up to set email alerts
|

Walking Trail Use among a Sample of Black, White, Hispanic, and Asian Adult Walkers

Abstract: Background: Walking trails are positively associated with physical activity; however, few studies have been conducted among diverse communities. We sought to describe trail use and the physical and social environmental correlates of trail use in a racially/ethnically diverse sample. Methods: We administered an on-site trail intercept survey to walkers on a trail (N = 175).We assessed frequency/duration of trail use, reasons for using the trail, perceptions of the trail, demographics and BMI. Results: Walkers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
4
3
0
Order By: Relevance
“…Barriers such as childcare obligations and lack of time and energy are frequently reported [ 39 ], but accessible recreational areas may lessen PA barriers by facilitating active living in everyday life (e.g., walking with strollers). In line with the present study, previous studies outside pregnancy indicate that associations between accessibility and walking behaviour is not modified by ethnicity or SEP [ 55 , 56 ]. In other words, initiatives to improve access to recreational areas may positively enhance health related behaviour, irrespective of ethnic and socio-economic background.…”
Section: Discussionsupporting
confidence: 93%
“…Barriers such as childcare obligations and lack of time and energy are frequently reported [ 39 ], but accessible recreational areas may lessen PA barriers by facilitating active living in everyday life (e.g., walking with strollers). In line with the present study, previous studies outside pregnancy indicate that associations between accessibility and walking behaviour is not modified by ethnicity or SEP [ 55 , 56 ]. In other words, initiatives to improve access to recreational areas may positively enhance health related behaviour, irrespective of ethnic and socio-economic background.…”
Section: Discussionsupporting
confidence: 93%
“…21 Of note, walkers attribute the social aspects of participating in a walking group, to their sustained walking and participation in the group, 21 underscoring the benefit of group activity. Consistent with recent research, 22 no gender-based differences were observed in terms of miles walked. A recent Texasbased study examining walking trail use 22 found both men and women reported spending similar amounts of time spent on the trail and reported using trails at a similar frequency.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with recent research, 22 no gender-based differences were observed in terms of miles walked. A recent Texasbased study examining walking trail use 22 found both men and women reported spending similar amounts of time spent on the trail and reported using trails at a similar frequency. These findings are promising, as they suggest that the new opportunities to trail walk in safe environments in the region may yield increases in physical activity for both men and women.…”
Section: Discussionsupporting
confidence: 92%
“…However, the present study found that isolates unique to in situ cultivation grew stably under the same conditions as those of the SDP cultivation at the sub cultivation step, which lacks such growth components. This phenomenon also occurred in previous studies that used in situ cultivation ( Bollmann et al, 2007 ; Jung et al, 2013 , 2014 , 2018 ). Only the difference between the in situ and SDP cultivation methods in the experimental procedure was whether a 1 week incubation was performed in the natural environment (inside the marine sponge in this study) prior to agar plate cultivation ( Figure 1a ).…”
Section: Discussionsupporting
confidence: 78%
“…Applying this idea to microbial cultivation led to developing in situ cultivation methods aiming to better simulate the natural environment (for a review, see Epstein et al, 2010 ). Several in situ cultivation methods with similar basic concepts have been applied to various environments, including sediment, activated sludge, alkaline soda lakes, sponges, soil, and a hot spring environment, and have been demonstrated to be highly capable of microbial cultivation ( Bollmann et al, 2007 ; Aoi et al, 2009 ; Jung et al, 2013 , 2014 , 2016 , 2018 ; Steinert et al, 2014 ). Recently developed new in situ cultivation method, diffusion bioreactor revealed that this approach is still useful for the cultivation of previously uncultured bacteria ( Chaudhary et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%